Pengaruh PhET (Physics Education Technology) menggunakan Model Inkuiri Terbimbing terhadap Kemampuan Kognitif Siswa Sekolah Dasar - Zidni Alfian Barif; Nuriman Nuriman; Rizki Putri Wardani (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2025)
This study aims to analyze significant differences in the PhET (Physics Education Technology) with the use the Guided Inquiry model of in terms of students' cognitive abilities through science learning outcomes before and after being treated with PhET media using the Guided Inquiry model. The research method used quantitative methods of Quasi-Experimental type with Non-equivalent Control Group Design research design. The data collection tool used Pretest-Posttest questions totaling 25 items. The study population was all fifth grade students of SDN Tanggul Wetan 02, totaling 48 students. The results showed that there was a significant difference in the cognitive abilities of students who used PhET media assisted the Guided Inquiry model with the cognitive abilities of students who used conventional learning. There is a significant increase in cognitive abilities after being treated with the application of PhET media assisted by Guided Inquiry model with before being treated with the application of PhET media assisted by Guided Inquiry model. In general, there is a positive and significant effect (2 tailed) p = 0.513 > 0.05 from the application of PhET media using Guided Inquiry model in science practicum activities on the cognitive abilities of elementary school students.